Kamus sains dan teknologi - Hasnah Mohamad (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2008)
English-Malay and Malay-English dictionary of science and technology.
Malay and English.
Keywords: Science -- Dictionaries; Science -- Dictionaries -- Malay; Technology -- Dictionaries; Technology -- Dictionaries -- Malay